Faktor - Faktor yang Mempengaruhi Kecemasan Ibu Hamil di Puskesmas Simpang Timbangan Kecamatan Indralaya Utara Kabupaten Ogan Ilir Tahun 2025 - Sri Handayani; Putu Lusita Nati Indriani; Arie Anggraini; Ahmad Arif (JURNAL KESEHATAN TERAPAN, 2026)
A woman will experience changes, both physically and psychosocially during pregnancy. In early pregnancy, changes such as body posture and physiological processes that take place can affect the patient's condition, often causing anxiety, mood fluctuations, liver disorders, emotional disorders and even anxiety. The aim of this research is to determine whether there is a relationship between age, knowledge and husband's support influencing the anxiety of pregnant women at Simpang Timbangan Community Health Center, North Indralaya District, Ogan Ilir Regency in 2025. This research is a type of quantitative descriptive research that uses a cross-sectional approach. The population in this study were all pregnant women who visited the Simpang Timbangan Community Health Center, North Indralaya District, Ogan Ilir Regency in 2025 from January to April, with a total of 810 people with the total sample in this study being random sampling of 89 respondents. aThe results of the bivariate analysis showed that age had a ρ value of 0.009, knowledge had a ρ value of 0.004, husband's support had a ρ value of 0.032. The conclusion of this research is the relationship that influences anxiety in pregnant women at the Simpang Timbangan Community Health Center, North Indralaya District, Ogan Ilir Regency in 2025. Suggestions for health workers. It would be good for community health workers, especially midwives, to know the anxiety experienced by patients, especially pregnant women, and provide in-depth education regarding the anxiety experienced by pregnant women.